Neudesin in obesity and type 2 diabetes mellitus: the effect of acute fasting and weight reducing interventions - Kratochvilova, Helena; Lacinova, Zdenka; Klouckova, Jana; Kavalkova, Petra; Cinkajzlova, Anna; Trachta, Pavel; Krizova, Jarmila; Benes, Marek; Dolezalova, Karin; Fried, Martin; Vlasakova, Zuzana; Pelikanova, Terezie; et al. (Diabetes, metabolic syndrome and obesity, 2019)
CONTEXT: Neudesin has recently been identified as a novel regulator of energy expenditure in experimental animals; however, its role in humans remains unexplored. OBJECTIVE: The aim of this study was to assess the effects of obesity and type 2 diabetes mellitus (T2DM) along with selected weight reducing interventions on serum neudesin levels and adipose tissue mRNA expression. PATIENTS AND METHODS: Fifteen obese subjects with T2DM undergoing endoscopic duodenal-jejunal bypass liner (DJBL) implantation, 17 obese subjects (11 with T2DM, 6 without T2DM) scheduled for gastric plication (GP), 15 subjects with functional hypoglycemia subjected to 72-hour acute fasting (AF), and 12 healthy controls were included in the study. RESULTS: Baseline neudesin levels were comparable between all groups. DJBL increased neudesin at 6 and 10 months after the procedure (1.77±0.86 vs 2.28±1.27 vs 2.13±1.02 ng/mL, P=0.001 for baseline vs 6 vs 10 months) along with reduction in body weight and improvement of HbA1c without any effect on neudesin mRNA expression in subcutaneous adipose tissue. Conversely, GP did not affect neudesin levels despite marked reduction in body weight and improvement of HbA1c. In contrast, AF decreased neudesin levels during the entire period (1.74±0.54 vs 1.46±0.48 ng/mL, P=0.001 for baseline vs 72 hours) with no impact of subsequent re-alimentation on neudesin concentrations. CONCLUSION: Neudesin levels are differentially regulated during AF and chronic weight reduction induced by DJBL or GP. Further studies are needed to assess its possible significance in energy homeostasis regulation in humans.
Keywords: weight reduction; neudesin; acute fasting; type 2 diabetes mellitus; obesity; bariatric surgery; energy homeostasis